The effects of temperature on callus induction and regeneration in selected Malaysian rice cultivar Indica - Suraiya Mostafiz,; Alina Wagiran,; Nur Syafiqoh Johan,; Nur Saliha Abdullah Zulkifli,; Ng, Ja Ming (Penerbit Universiti Kebangsaan Malaysia, 2018)
The development of an efficient tissue culture protocol for somatic embryo would facilitate the genetic modification in breeding program. The present study describes the reproducible protocols for three wetland Malaysian rice cultivars (MR232, MR220 and MR220-CL2) and upland rice (Bario) via somatic embryogenesis. In the present study, four pre-heat treatments (35, 40, 45 and 50°C) were applied to mature seeds with different imbibition periods (3, 5 and 7 days) prior to culture on MS media with 3 mg/L 2,4-D. The results showed that the cultivars exhibited the highest callus induction percentage from 45°C pre-heated seeds and 3 days imbibition (100%, 96%, 100% and 95% for MR232, MR220, MR220-CL2 and Bario, respectively). Callus was induced early ranging from 3 to 12 days compared to without pre-heat treatment. The regeneration efficiency for MR220 and MR220-CL2 cultivars was significantly higher compared to the control treatment. However, both 45°C and 25°C (control) treatments produced higher plantlet regeneration for MR232 and Bario. This study observed that pre-heat treated seeds prior to callus induction did promote callusing and hence regeneration. These findings can be used to establish a suitable protocol for the in vitro regeneration system for several genetic improvements in the numerous stress tolerances of Malaysian rice.